Smart packaging—An overview of concepts and applications in various food industries. Issue 1 (8th February 2023) - Thirupathi Vasuki, Mithulesh; Kadirvel, Vijayasri; Pejavara Narayana, Gururaj
Abstract: Contamination of food may occur at any stage in the process from "farm to fork". The consumption of food contaminated with infectious bacteria, viruses and parasites, and noninfectious chemicals and toxins may cause over 200 diseases that range from diarrhea to cancers. Conventional packaging systems are sophisticated, and passive and only protect the environment. Currently, there is an elevation in new consumer demands such as improved communication capabilities in packaging systems. To satisfy the demand, smart packaging systems may be designed and employed. In this review, the mode of action adopted to ensure safety and security by various smart packaging techniques for food products such as fruits, vegetables, dairy products, baked goods, meat products, beverages, and space foods is discussed. Active packaging technology focuses on maintaining the quality and enhancing the shelf‐life of food products. The elements of active packaging systems meet up the real market needs by incorporating functional agents into the packaging material. Intelligent packaging technology indicates the freshness, quality, safety, and security of food products and posses quality identification systems to effectively communicate with consumers. This review aims to analyze and interpret the concept of smart packaging systems, consumer perception, and their application in various food sectors. Abstract : The review article gives a complete picture of food packaging innovations in various sectors of food and its related research.